Monochorionic-Diamniotic Twin Pregnancy Complicated by Spontaneous Septostomy and Cord Entanglement: A Systematic Review, Evaluation of Complication Rates and Presentation of an Additional Case - Chiara Boccherini; Valentina D’Ambrosio; Eleonora Marcoccia; Flaminia Vena; Daniele Di Mascio; Sara Corno; Martina Bartolone; Antonella Giancotti (Clinical and Experimental Obstetrics & Gynecology, 2022)
Background: Our purpose is to describe the ultrasound findings, both with bi-dimensional and three-dimensional imaging, suggestive of spontaneous septostomy in monochorionic-diamniotic twin pregnancies. Methods: PubMed, Medline and reference lists were searched using “Spontaneous septostomy and twin pregnancy” as keywords. Seventeen articles reporting a total of 25 cases, adding our own, were included in the systematic review. Only English full text articles, the main purpose of which was to describe spontaneous septostomy in twin pregnancies, were included. Results: In our sample the major ultrasound sign arousing suspicion of spontaneous septostomy was found to be an absent or disrupted inter-twin membrane (79% of cases). Twins close to each-other were described in 33% of cases, while cord entanglement was suspected only in 27% of cases. We reported a lower antenatal detection of entanglement when compared with intrapartum evaluation (27% vs 59%). Adverse fetal outcomes occurred in 12% of cases, while 88% of cases were born alive. Conclusions: Spontaneous septostomy represents a diagnostic and clinical challenge for obstetrics providers. Clinicians must focus on ultrasound findings to close surveil fetal wellness and reduce both fetal and neonatal impairment.